2014
DOI: 10.2117/psysoc.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Places and Traces of Personality

Abstract: Personality psychology and socioecological research are kindred spirits in their investigation of person-environment transactions at different levels of analysis. In the present article, we provide an overview of empirical findings that substantiate the links between personality variation and (social) environment structures at both macro and individual levels of analysis. In doing so, we are particularly concerned about the role of geographical mobility; thus, we explore the conditions that bring it into effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Specifically, Zimmermann and Neyer (2014) examine the transaction between personality and geographical mobility, specifically, the influence of living abroad and personality on interpersonal relationships, as well as the influence of personality on choosing to live abroad. Importantly, Zimmermann and Neyer's work showed that the influence of personality on relationship was mediated by selective migration, such that students' openness to experience and extraversion influenced their likelihood of choosing to study abroad, which in turn influenced changes in their social networks (Zimmermann & Neyer, 2014). Mizokawa and Komiya (2014) explore the role of social environments on the emergence of theory of mind.…”
Section: The Current Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Zimmermann and Neyer (2014) examine the transaction between personality and geographical mobility, specifically, the influence of living abroad and personality on interpersonal relationships, as well as the influence of personality on choosing to live abroad. Importantly, Zimmermann and Neyer's work showed that the influence of personality on relationship was mediated by selective migration, such that students' openness to experience and extraversion influenced their likelihood of choosing to study abroad, which in turn influenced changes in their social networks (Zimmermann & Neyer, 2014). Mizokawa and Komiya (2014) explore the role of social environments on the emergence of theory of mind.…”
Section: The Current Issuementioning
confidence: 99%
“…For instance, the articles by Oka (2014) and by Gross and Proffitt (2014) both explored the role of geographical terrains. Murray (2014), Oka (2014), and Gross and Proffitt (2014) all explored physical environments, whereas Mizokawa and Komiya (2014) and Zimmermann and Neyer (2014) both explored interpersonal environments. Importantly, from the socio-ecological perspective, there are many possibilities of cross-fertilization of research across traditional demarcations, such as those featured in this issue-namely, clinical, perception, developmental, personality, and evolutionary psychology.…”
Section: Cross-fertilization Via Socio-ecological Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Corresponsive Principle of personality development states that certain personality characteristics select or elicit relationship experiences (i.e., the selection effect), which reinforce these specific characteristics (i.e., the socialization effect; Roberts & Wood, 2006; Roberts, Wood, & Caspi, 2008). Zimmermann and Neyer (2013, 2014) showed that more open students were more likely to go abroad for a semester and gain new friendships, which then predicted further increases in openness. To date, dynamic transactions between personality and friendships have mainly been studied in adolescence and young adulthood, but hardly addressed in middle and late adulthood.…”
Section: Co-development Of Personality Traits and Friendships: An Emp...mentioning
confidence: 99%
“…Personality traits change substantially during young adulthood (Lüdtke et al, 2011; Roberts, Walton, & Viechtbauer, 2006), but the reported socialization effects of both friendships and family relationships are often small or nonsignificant (Asendorpf & Wilpers, 1998; Mund & Neyer, 2014; Neyer & Lehnart, 2007, Table 2). Only one study – which used the comparably shorter interval of 1 year – reported moderate socialization effects for friends when young adults entered new contexts during an academic exchange year in college (Zimmermann & Neyer, 2014). The lack of family socialization effects during this time concurs with our hypotheses (Figure 1b), as parents and other relatives lose their influence as adolescents mature and achieve greater autonomy.…”
Section: Co-development Of Personality Traits and Friendships: An Emp...mentioning
confidence: 99%